2021
DOI: 10.1016/j.arabjc.2021.103393
|View full text |Cite
|
Sign up to set email alerts
|

Potential bioactive compounds as SARS-CoV-2 inhibitors from extracts of the marine red alga Halymenia durvillei (Rhodophyta) – A computational study

Abstract: The respiratory infection COVID-19 caused by the virus SARS CoV-2 has continued to be a major health problem worldwide and has caused more than a million mortalities. Even if the development of COVID-19 vaccines has shown much progress, efforts to find novel, natural anti-viral drugs should be pursued. Halymenia durvillei is a marine red alga widely distributed around Southeast Asia. This study aimed to develop new anti SARS CoV-2 compounds from ethanolic and ethyl acetate extracts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The GC-MS analysis of the C. racemosa extract identified a total of 92 active compounds, most of which were fatty acids and alkanes, typically the most prominent phytochemicals in this seaweed ( Table S1 ). The profile of bioactive compounds obtained in this present study are similar to those identified previously in the red alga Halymenia durvillei , where 37 compounds where identified, most of which were fatty acids [ 10 ]. Lipids may act antagonistically to viral infection by direct inhibition or by regulating adaptive and inflammatory responses [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The GC-MS analysis of the C. racemosa extract identified a total of 92 active compounds, most of which were fatty acids and alkanes, typically the most prominent phytochemicals in this seaweed ( Table S1 ). The profile of bioactive compounds obtained in this present study are similar to those identified previously in the red alga Halymenia durvillei , where 37 compounds where identified, most of which were fatty acids [ 10 ]. Lipids may act antagonistically to viral infection by direct inhibition or by regulating adaptive and inflammatory responses [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Macroalgae have been proposed in prevention and treatment of COVID-19, including Porphyra umbilicalis, Caulerpa racemosa , and Gelidium sp. [ 10 ]. Of these, the green seaweed C. racemosa is native to South Sulawesi where it is called lawi-lawi and tends to be abundant in shallow coastal water [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Moreover, the discovery of active compounds from natural products remains one of the most important sources for developing novel anti-CoV agents. [41][42][43][44][45][46][47] Therefore, many research groups have devoted their efforts to finding anti-CoV agents in naturally occurring compounds. [48][49][50][51][52] To date, a variety of marketed drugs and other structurally diverse synthetic compounds, as well as a number of natural compounds, have been found to be efficacious inhibitors of SARS-CoV-2 3CL pro , showing great potential for developing novel broad-spectrum anti-CoV agents.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiple drug discovery strategies have been utilized to find or develop a number of 3CL pro inhibitors against SARS‐CoV‐2, such as drug repurposing, virtual screening coupled with high‐throughput screening (HTS), and structure‐based drug design 38–40 . Moreover, the discovery of active compounds from natural products remains one of the most important sources for developing novel anti‐CoV agents 41–47 . Therefore, many research groups have devoted their efforts to finding anti‐CoV agents in naturally occurring compounds 48–52 .…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed nutraceutical bioactive compounds have great potential in biomedical and pharmaceutical applications [85][86][87][88][89][90][91][92]. Phytochemical analysis of Bornean seaweeds indicated the presence of various nutraceutical bioactive compounds with different properties, including phenolics, flavonoids, alkaloids, alcohols, steroids, fatty acids, terpenoids, etc.…”
Section: Nutraceutical Profiling Of North Bornean Seaweedsmentioning
confidence: 99%